Changing nature of operational modes in international business : information and communication technologies and its impact on communication, coordination, cooperation and control. - Tan, James Hwan Kuok. (2008)
This project explores the various foreign market entry modes and the developments of Information & Communication Technologies (ICT). Specifically, it aims to explain and provide insights on the uses of ICT and its impact on some of companies’ main concerns when doing international business, which are known as the 4 Cs, namely - communication, coordination, cooperation and control.